Torsional Rigidities of Cancellous Bone Filled with Marrow: The Application of Multipoint Pads Approximants - Tokarzewski, S.; Telega, J.J.; Gałka, A. (Engineering Transactions, 2001)
An idealized model of prism-like trabecular bone was developed to study its static and dynamic responses under torsional moments. Effects of bone marrow and bone apparent density were investigated. By constructing multipoint Pade approximants [1, 2] to the torsional complex modulus, hydraulic stiffening of the prism-like bone due to the presence of bone marrow was predicted. The torsional compliance, creep function and relaxation function were also evaluated.